Nature's value: Evidencing a Moldovan terroir through scientific infrastructures - Daniela Ana (Ethnos, 2024)
Terroir can increase the exchange value of wine in competitive markets in global capitalism. Relying on ethnographic research in Moldova, this article shows how value is produced through infrastructures that evidence the environmental features of a wine's place of origin in the form of terroir. In these processes, genericness and uniqueness prove to be mutually constitutive. While the Soviet wine industry used evidencing infrastructures such as laboratories and measuring devices to produce decent and affordable table wine, old infrastructures have been adapted and new ones introduced to evidence terroir through analyses of soils and yeasts. The focus on scientific infrastructures of value connects new and historical materialist approaches in the conceptualisation of human-environment relations. It contributes to a new historical materialist understanding of value by highlighting the interrelation of political economic, environmental and technological dimensions in the making of terroir, through evidencing, measuring and standardising physical features of the environment.
Keywords: 630; infrastructure; Moldova; soils; terroir; yeasts